2015
DOI: 10.1177/1933719115589409
|View full text |Cite
|
Sign up to set email alerts
|

Ulipristal Acetate Antagonizes the Inhibitory Effect of Progesterone on Ciliary Beat Frequency and Upregulates Steroid Receptor Expression Levels in Human Fallopian Tubes

Abstract: Ulipristal acetate (UPA) is a new selective progesterone receptor (PR) modulator used for emergency contraception. However, our understanding of its mechanisms of action on oviductal cilia is limited. The present study focused on the in vitro effects of UPA (0.1, 1, and 10 μmol/L) on the cilia and steroid receptors of human fallopian tubes. The ciliary beat frequency (CBF), the ultrastructure of cilia, and the levels of steroid receptors were measured. The effects of UPA on the progesterone-induced CBF reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…In addition, we have investigated that the number of epithelial cells of the mucosa of the uterine tube (secretory, basal, ciliated) is not the same throughout the length of the uterine tube of both human and white rats. The largest number of cilia in the fimbriae and ampulla gradually decreases in the direction of the uterus, and the secretory cells are the smallest in the fimbriae and ampulla, and most in the uterine part, which is consistent with the literature [2,25]. As for the structure of the subserosa, there are also several thoughts.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, we have investigated that the number of epithelial cells of the mucosa of the uterine tube (secretory, basal, ciliated) is not the same throughout the length of the uterine tube of both human and white rats. The largest number of cilia in the fimbriae and ampulla gradually decreases in the direction of the uterus, and the secretory cells are the smallest in the fimbriae and ampulla, and most in the uterine part, which is consistent with the literature [2,25]. As for the structure of the subserosa, there are also several thoughts.…”
Section: Discussionsupporting
confidence: 88%
“…Our results suggest that UPA does not downregulate PR expression in uterine myomas but instead may prevent the turnover required for their appropriate activity, thereby explaining the antagonist action of UPA. This blockage in PR recycling might also account for the accumulation of PRs seen in the presence of SPRMs reported by other investigators [31, 38-40]. …”
Section: Discussionmentioning
confidence: 72%
“…However, in a murine model of myoma xenografts, PR expression was found to be unchanged after mifepristone treatment [31], probably thanks to the conferred protection against proteasomal degradation [37]. UPA treatment even increased PR expression in 2 models of breast cancer xenografts [38, 39], as well as in the Fallopian tubes [40] and normal endometrium [41-43]. Our results suggest that UPA does not downregulate PR expression in uterine myomas but instead may prevent the turnover required for their appropriate activity, thereby explaining the antagonist action of UPA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast Yuan et al (2015) showed that UPA does not directly affect CBF or the ultrastructure of the cilia, but it dose-dependently antagonized the progesterone-induced CBF decrease. To prove the hypothesis of a progesterone antagonist action the authors highlighted that: Mifepristone, an antagonist of the PR, inhibits progesterone-induced CBF reduction ( Mahmood et al, 1998 ); UPA has been shown to be a progesterone antagonistic without agonistic activity in most studied published ( Attardi et al, 2002 ; Chabbert-Buffet et al, 2005 ; Xu et al, 2008 ; Communal et al, 2012 ; Ko et al, 2014 ) and finally, their study demonstrates that UPA is able to up-regulate the expression levels of the estrogen receptor (ER) and the PR in the fallopian tubes, while progesterone down regulates them ( Horne et al, 2009 ).…”
Section: Effects On the Fallopian Tubementioning
confidence: 76%
“…Secondly, in studies on UPA effects on the fallopian tube ( Li et al, 2014 ; Yuan et al, 2015 ) is unclear how it affects fertilization and/or transport of the fertilized egg and therefore the embryo implantation.…”
Section: Discussionmentioning
confidence: 99%